الحواضر الثقافية في الجزائر خلال العهد العثماني (تلمسان وبجاية أنموذجا) - أشواق فتح الله (My University, 2025)
Abstract: In conclusion, during the Ottoman period, Algeria witnessed a remarkable intellectual flourishing in some of its cultural centers, particularly Tlemcen and Béjaïa. These two cities rose to the rank of major cultural and intellectual hubs in the Islamic Maghreb. This prosperity was reflected in the intellectual advancement achieved by both Béjaïa and Tlemcen, evident in the abundance of educational institutions that attracted large numbers of students and scholars, as well as in the prolific intellectual output covering various fields. This scientific and cultural dynamism gave Tlemcen and Béjaïa a distinctive intellectual radiance, establishing them as prominent centers of knowledge within and beyond the central Maghreb. ------------------------------ الملخص وخلاصة القول أن الجزائر خلال الفترة العثمانية عرفت بعض حواضرها ازدھارا ملحوظا من الجانب الفكري في مقدمتها تلمسان وبجاية فقد ارتقت هاتين الحاضرتين إلى مصاف الحواضر والمراكز الثقافية الكبرى في المغرب الإسلامي، وقد تجلى هذا الإزدهار في الرقي الفكري الذي بلغته كل من بجاية وتلمسان من خلال كثرة دور التعليم التي كانت تستقطب أعداد كبيرة من الطلاب والعلماء وكذلك كثرة الإنتاج الفكري الذي شمل میادین متعددة. وقد أضفى هذا الحراك العلمي على تلمسان وبجاية طابعا اشعاعیا خاصا جعل منهما مركزين مرموقين للعلم والمعرفة داخل المغرب الاوسط وخارجه. -------------------------- Résumé: En résumé, l’Algérie, durant la période ottomane, a vu certaines de ses principales villes connaître un essor intellectuel remarquable, notamment Tlemcen et Béjaïa. Ces deux cités ont accédé au rang des grands centres culturels du Maghreb islamique. Cet essor s’est manifesté à travers le développement intellectuel qu’ont connu Tlemcen et Béjaïa, illustré par le grand nombre d’écoles et d’institutions éducatives qui attiraient un large public d’étudiants et de savants, ainsi que par une riche production intellectuelle couvrant divers domaines du savoir. Ce dynamisme scientifique a conféré à Tlemcen et à Béjaïa un rayonnement culturel particulier, faisant d’elles des pôles prestigieux du savoir et de la connaissance, tant au sein du Maghreb central qu’au-delà.
Keywords: الحواضر الثقافية ، العهد العثماني، تلمسان – بجاية